Predicting the probability of violence in actor–target relational dyads: Self-control and interpersonal provocations as mutual properties - Schreck, Christopher J. (The British journal of criminology, 2021)
If disputes are ever-present in human interaction, all relational dyads contain potential offenders and targets. We theorize that each dyad partner’s self-control independently influences the likelihood of violence and that low self-control will express itself in provocative behaviour. Using two waves from the Interpersonal and Conflict Resolution survey, with measures collected from each member of 443 couples, we create dyads and analyse the independent contributions of the specified variables for both would-be offenders and the potential target. We found that a potential target with low self-control was more likely to be attacked by the actor, irrespective of the actor’s self-control. This effect was explained by a tendency of both partners to engage in verbally provocative behaviour. These results are supportive of self-control theory’s predictions concerning the importance of target decision-making and indicate that other criminological theories can profit from considering the target’s role in violent crime causation.